Research of loading ability, wear and longevity of conical oblique-touth involute transmissions during two-pair hooking. Part 2. The influence of transmission relation - Чернець, М.В.; Береза, В.В.; Чернець, Ю.М. (Problems of Tribology, 2014)
The influence of transmission relation of gear on the value of maximal contact pressures, wear of wheel teeth and minimal longevity of gear in dependence of the angle of tooth slope was investigated. The regularities of this influence have been revealed presented graphically.